Determining the ability to differentiate results between independent sun protection factor tests using the ISO24444 method - Bacardit, Aleix (Frontiers in Medicine, 2023)
Introduction: The sun protection factor has nowadays become a familiar metric to understand sunscreen effectiveness. This value is displayed on the label of sunscreens and it is established by translating the results obtained from standardized testing methods to regulatory labeling criteria. The ISO24444, a widely accepted method to measure the sun protection factor, is designed to determine the validity of a single test, but it lacks criteria to compare results and many regulators only endorse the method as a valid means to label sunscreens. This supposes a challenge for manufacturers and regulators routinely using the method to take decisions on product labeling when confronted with disparate results for the same product. Method: Analytical review of the statistical criteria used by the method to determine test validity. Results: For the same product, results from independent tests (of 10 subjects each) separated less than 1.73 can be considered as the same from the point of view of compliance to the standard. Conclusion: This range of sun protection factor values far exceeds the ranges for labeling and categorizing sunscreens as per current regulations and thus opens the possibility that sunscreens are unknowingly mislabeled. These findings can be summarized in a “discriminability map” to assist comparing results from different tests and to better inform the labeling of sunscreen products and thus increase confidence to prescribers and consumers.